SERVICE EFFECTIVENESS OF PANDAWA BPJS KESEHATAN IN NGANJUK REGENCY - Nurmitasari; Syarifah, Ina; Hernando, Hendrick (Epicheirisi: Jurnal Manajemen, Administrasi, Pemasaran dan Kesekretariatan, 2023)
Information and communication services in the service industry context have a crucial role. BPJS Kesehatan, as a national health insurance institution, provides Pandawa service to accommodate administrative needs and participant complaints. This study was conducted to assess the effectiveness of Pandawa service usage in Nganjuk Regency. We applied four indicators to achieve that objective, including interface, navigation, content, and reliability. A total of 50 BPJS Kesehatan participants were involved as respondents in this study. Based on the data interpretation results, it was concluded that the Pandawa BPJS Kesehatan in Nganjuk Regency was in the effective category.